The Use of Digital Technology in Adolescents in Islamic Religious Learning: An Interdisciplinary Approach - Suwarni Jayanti; Ma'rifah Ma'rifah; Sampara Palili (Early Publishing, 2025)
This study aims to analyze the use of digital technology in Islamic religious learning with an interdisciplinary approach involving the disciplines of education, psychology, technology, and Islamic studies. The research uses a research study method with a descriptive qualitative approach that emphasizes the understanding of phenomena, practices, and perceptions of teachers and students in a real context. Data was collected through observation, in-depth interviews, documentation, and literature studies, then analyzed thematically with reduction, presentation, triangulation, and verification procedures. The results of the study show that digital transformation has changed the learning method from lectures and face-to-face to interactive learning based on digital platforms such as LMS, Google Classroom, Zoom, and Islamic applications. The interdisciplinary approach ensures the integration of pedagogical, psychological, technological, and Islamic values so that learning is more innovative, humanistic, and relevant. Digital technology has been proven to increase access to religious information, learning motivation, flexibility, collaboration, and evaluation effectiveness, although it still requires digital literacy and teacher supervision. Thus, digital technology becomes a strategic instrument in improving the quality of Islamic learning that is adaptive, inclusive, and based on spiritual values.